Performance enhancement of latent energy storage system using effective designs of tubes and shell - Rehan Qaiser; Muhammad Mahabat Khan; Hassan Farooq Ahmed; Faraz Kaiser Malik; Muhammad Irfan; Inam Ul Ahad (Energy Reports, 2022)
This study aims to numerically investigate the effects of geometric designs of tubes and shell on thermal performance enhancement of latent thermal energy storage system (LTESS). Stearic acid is used as a phase change material (PCM) while water acts as heat transfer fluid (HTF). Starting with a base case consisting of three circular HTF tubes within a circular shell, the tube and shell geometries are modified systematically. First, the effect of tube shapes and their orientations are investigated in detail. The circular exteriors of HTF tubes are modified with hexagonal, pentagonal, square and triangular shapes. The performance of triangular tubes with the vertex pointing downward exceeds all the other tube configurations. It augments the melting rate of the PCM by 27.2% and the energy storage capacity of the LTESS by 3.72%, as compared to the base case. The bottom vertex angle of the best HTF tube design is then varied yielding 45∘as the optimum triangular tube configuration. It improves the energy storage capability of the LTESS by 7.61% and the melting rate of the PCM by 41.4%. Following the optimum HTF tube design, the triangulated shell designs with various bottom vertex angles are explored. The 75∘bottom vertex angle of the shell offers maximum improvement. It accelerates the melting rate of the PCM by 66.9% while enhancing the energy storage capacity of the LTESS by 23.7% in comparison to the base case. Lastly, two new correlations of melting Fourier number and average Nusselt number are proposed for the optimum LTESS design configuration.